DNA Methylation Influences Chlorogenic Acid Biosynthesis in Lonicera japonica by Mediating LjbZIP8 to Regulate Phenylalanine Ammonia-Lyase 2 Expression - Zha, Liangping; Liu, Shuang; Liu, Juan; Jiang, Chao; Yu, Shulin; Yuan, Yuan; Yang, Jian; Wang, Yaolong; Huang, Luqi (Frontiers in Plant Science, 2017)
The content of active compounds differ in buds and flowers of Lonicera japonica (FLJ) and L. japonica var. chinensis (rFLJ). Chlorogenic acid were major active compounds of L. japonica and regarded as measurements for quality evaluation. However, little is known concerning the formation of active compounds at the molecular level. We quantified the major chlorogenic acid (CGAs) in FLJ and rFLJ, and found the concentrations of CGAs were higher in the buds of rFLJ than those of FLJ. Further analysis of CpG methylation of CGAs biosynthesis genes showed differences between FLJ and rFLJ in the 5′-UTR of phenylalanine ammonia-lyase 2 (PAL2). We identified 11 LjbZIP proteins and 24 rLjbZIP proteins with conserved basic leucine zipper domains, subcellular localization and electrophoretic mobility shift assay showed that the transcription factor LjbZIP8 is a nuclear-localized protein that specifically binds to the G-box element of the LjPAL2 5′-UTR. Additionally, a transactivation assay and LjbZIP8 overexpression in transgenic tobacco indicated that LjbZIP8 could function as a repressor of transcription. Finally, treatment with 5-azacytidine decreased the transcription level of LjPAL2 and CGAs content in FLJ leaves. These results raise the possibility that DNA methylation might influence the recruitment of LjbZIP8, regulating PAL2 expression level and CGAs content in L. japonica.